INTERPRETIVE DISTANCE BETWEEN ACCOUNTING INFORMATION AND INSTITUTIONAL STRATEGY: A HERMENEUTIC PHENOMENOLOGICAL STUDY ON PUBLIC SERVICE AGENCY UNIVERSITIES - Aditiya, Roby; Damayanti, Ratna Ayu; Said, Darwis (ISAFIR: Islamic Accounting and Finance Review, 2025)
This study aims to explore the meaning and practice of using accounting information in strategic decision making at Public Service Agency State Universities (PTN-BLU). This study arises from the phenomenon of low utilization of accounting information in public sector managerial practices and the limitations of the positivistic approach in understanding this context. Using an interpretive approach and hermeneutic phenomenological method, data were collected through in-depth interviews and document analysis, involving two key informants from internal control and strategic planning units. The results showed four main findings: accounting information is understood administratively and not strategically; there is a distance between accounting systems and policy logic; strategic decisions are dominated by bureaucratic and political narratives; and there is a weak interpretive culture of financial statements. The study asserts that accounting reform should go beyond technical aspects and emphasize the importance of interpretation of financial statements.